Historical Perceptions about Children and Film: Case Studies of the British Board of Film Censors, the British Film Institute, and the Children’s Film Foundation from the 1910s to the 1950s - Terui Takao (Open Cultural Studies, 2024)
This article explores how ideas regarding children and film were shaped and shifted from the 1910s to the 1950s by consulting three critical moments and key institutions: the British Board of Film Censors in the 1910s, the British Film Institute in the 1930s, and the Children’s Film Foundation in the 1950s. By doing so, the article elucidates how discourse and ideas about children’s films and audiences have transformed, resulting in policy shifts from restrictive to encouraging approaches that appreciate children’s tastes and the entertainment value of children’s cinema. Based on comparative historical research, this article empirically reveals that perceptions of children’s cinema have changed throughout history and that the policy documents offer significant materials to explain this.